Analysis of TikTok Content Strategy in Increasing Audience Engagement on Asset Management PT Sinergi Mitra Investama - Arum Cayafatika; Elok Vilantika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze TikTok content strategies to increase audience engagement in TikTok Asset Management Division PT Sinergi Mitra Investama. The basis of this research is the shift in marketing strategy from conventional to digital marketing, as well as the suboptimal use of TikTok as a promotional platform. This research uses a descriptive qualitative approach with a case study method. Data collection was conducted through in-depth interviews, observation, and documentation, involving four informants: digital marketing staff, asset management division staff, and social media admins. The results show that TikTok content strategies have been implemented through asset promotion, narratives, and trends, but their implementation is less effective due to limited human resources, unstructured content planning, and less than optimal use of data analytics. Content with storytelling and trend elements has proven more successful in increasing audience engagement than formal promotions. Conclusion: TikTok content strategies have great potential to increase interaction and asset rentals if supported by consistent planning, visual quality, and data-driven evaluation.